2006
DOI: 10.1128/jcm.01887-06
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening of Topoisomerase Gene Mutations by a Novel Melting Curve Analysis Method for Early Warning of Fluoroquinolone-Resistant Streptococcus pneumoniae Emergence

Abstract: We developed a real-time PCR assay combined with melting curve analysis for rapidly genotyping quinolone resistance-determining regions (QRDR) of topoisomerase genes in Streptococcus pneumoniae. This assay was not only accurate for the screening of fluoroquinolone (FQ) resistance but also relevant as an early warning system for detecting preexisting single QRDR mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…As shown in Table 4, the mutation profiles for the QRDRs in the gyrA and parC genes revealed a close relationship between the MIC level and the number of QRDR mutations. Previous studies have found that the conventional phenotypic method failed to detect strains that have a single QRDR mutation; these strains have the potential to develop into a highly resistant pathogen (8). Several reports have noted that a significant number of Streptococcus pneumoniae isolates already have a single-step mutation and are prone to acquiring a second-step mutation (19).…”
mentioning
confidence: 99%
“…As shown in Table 4, the mutation profiles for the QRDRs in the gyrA and parC genes revealed a close relationship between the MIC level and the number of QRDR mutations. Previous studies have found that the conventional phenotypic method failed to detect strains that have a single QRDR mutation; these strains have the potential to develop into a highly resistant pathogen (8). Several reports have noted that a significant number of Streptococcus pneumoniae isolates already have a single-step mutation and are prone to acquiring a second-step mutation (19).…”
mentioning
confidence: 99%
“…Isolates D001 and D002 had both GyrA and ParC mutations (for D001, Ser79Phe in ParC and Gly85Lys in GyrA; for D002, Ser79Phe in ParC and Ser81Phe in GyrA). All the strains were exposed to 2,4,8,16,32, and 64ϫ the MICs for ciprofloxacin (CIP), LVX, GAT, MXF, and GAR for 48 to 72 h at 37°C in 5% CO 2 . The MPCs were measured using a procedure previously described (2).…”
mentioning
confidence: 99%
“…However, this is highly improbable, since molecular typing of 9 of these Several real-time PCR methods based on the detection of point mutations have been developed to differentiate between drug-susceptible and -resistant bacteria (4,6,12,14,15,16). However, to the best of our knowledge, only two real-time PCR assays followed by high-resolution melt (HRM) curve analysis have been developed to track antibiotic resistance in Mycoplasma pneumoniae (12,15), both for macrolides.…”
Section: Discussionmentioning
confidence: 99%